2018
DOI: 10.17576/mjas-2018-2203-11
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHEMICAL SCREENING, ANTIFUNGAL AND ANTIBACTERIAL ACTIVITIES OF Musa acuminata PLANT

Abstract: Musa acuminata plant is known for its edible fruits and the uses of its leaves as food wrapper in industries. Exploring it medicinal values will be an advantage because it can easily grow in Malaysia. The non-edible part which is the leaves of Musa acuminata 'Dwarf Cavendish' plant is analysed to determine the phytochemical constituents and antimicrobial properties. Two types of organic solvents used namely hexane and methanol. The antimicrobial properties of the extract produced were tested against Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Although pseudo-stem extract showed no impact on many fungal species (Kumar et al, 2014), banana leaves showed considerable antifungal activity, with the widest inhibition zone diameters against species such as Penicillium, Candida, and Alternaria sp. (Bankar & Dole, 2016;Bisht et al, 2016;Harith et al, 2018). Methanol extract exhibited a higher percentage of inhibition than ethanol extract, followed by ethyl acetate.…”
Section: Antifungal Activitymentioning
confidence: 97%
“…Although pseudo-stem extract showed no impact on many fungal species (Kumar et al, 2014), banana leaves showed considerable antifungal activity, with the widest inhibition zone diameters against species such as Penicillium, Candida, and Alternaria sp. (Bankar & Dole, 2016;Bisht et al, 2016;Harith et al, 2018). Methanol extract exhibited a higher percentage of inhibition than ethanol extract, followed by ethyl acetate.…”
Section: Antifungal Activitymentioning
confidence: 97%
“…The concentrations of 40 and 60 mg/mL banana leaf extract were most effective against T. mentagrophytes , which exhibited a 5 mm diameter inhibition zone. Nystatin was utilized as a positive control against T. mentagrophytes , which showed lesser effects on the colonies of fungi by producing a 2 mm zone (Harith et al, 2018).…”
Section: Pharmacological Importance Of Banana and Its By‐productsmentioning
confidence: 99%